(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study is being conducted to observe the effectiveness of training and to see the real benefits of training over the performance of micro, small and medium enterprises. Though, in past several studies have been conducted in the western context only and there are certain inconsistencies in the findings. This study is expected to be the first of its kind in the Asian context covering micro, small, and medium enterprises simultaneously. This research applied ANOVA for analyzing the effectiveness of the worker’s training regarding improvement in performance of the enterprises. A sample of 100 micro small and medium enterprises was analyzed. The findings identified that all the eight areas chosen for the analysis of improvement in performance, because of effectiveness of training, have proven significantly effective. Secondly, on the job training is most successful for the micro, small, and medium enterprises regardless of their size. The study has methodological and practical significance. The study identified the methods of training that are successful in the context of developing countries.